PERANAN ARCA CATUḤKĀYPERANAN ARCA CATUḤKĀYA PADA MASA BALI KUNOA PADA MASA BALI KUNO: Fungsi dan Makna arca catuḥkāya pada masa Bali Kuno - Rajeg, Kadek Dedy Prawirajaya; Purwanto, Heri; Titasari, Coleta Palupi (BRIN, 2023)
Catuḥkāya is a monolithic statue featuring four human figures carved on its sides, representing the cardinal directions: south, east, north, and west. This study examined the function and meaning of catuḥkāya statues in ancient Balinese. Data collected from field surveys and literature reviews was analyzed with the iconographic and comparative approach. Study results’s shows that the catuḥkāya statue is the development of Mukhaliṅga. In the past, the catuḥkāya statue was most likely part of the Shiva Tantrayana’s ritual and used for abhicāra (ceremonies for destroying enemies). The meaning implied in the catuḥkāya statue is the embodiment of universe (microcosm and macrocosm) consist of soft form (tānmatra) and rough form (mahābhūta).